2014
DOI: 10.1177/0886260514555866
|View full text |Cite
|
Sign up to set email alerts
|

Affective Dispositions and PTSD Symptom Clusters in Female Interpersonal Trauma Survivors

Abstract: Interpersonal trauma (IPT) against women can have dire psychological consequences including persistent maladaptive changes in the subjective experience of affect. Contemporary literature has firmly established heightened negative affect (NA) as a risk and maintenance factor for posttraumatic stress disorder (PTSD). However, the relationship between NA and PTSD symptoms is not well understood within IPT survivors, the majority of whom are female, as much of this research has focused on combat veterans. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…Some studies have also found that traumatic fear can lead to higher levels of PTSD (e.g. Brown et al, 2016;Kleim et al, 2013;Najavits et al, 2006;VanElzakker et al, 2014;Wang, Wu, & Lan, 2020;Zalta et al, 2014). Therefore, traumatic exposure may have an indirect effect on PTSD via fear.…”
mentioning
confidence: 99%
“…Some studies have also found that traumatic fear can lead to higher levels of PTSD (e.g. Brown et al, 2016;Kleim et al, 2013;Najavits et al, 2006;VanElzakker et al, 2014;Wang, Wu, & Lan, 2020;Zalta et al, 2014). Therefore, traumatic exposure may have an indirect effect on PTSD via fear.…”
mentioning
confidence: 99%
“…The association between general negative affect and posttraumatic stress disorder (PTSD) has been well established (Brown et al, 2016;Marshall-Berenz, Morrison, Schumacher, & Coffey, 2011;Souza et al, 2008). Moreover, although PTSD was originally conceptualized principally as a disorder of fear (American Psychiatric Association [APA], 1980;Foa & Kozak, 1986), there has been increasing recognition that negative emotions beyond fear are also strongly associated with PTSD This work was supported by the Brain and Behavior Research Foundation (Narsad Young Investigator Award to TG; 23524), The Moshe Hess Foundation (TG and MG), NATAL: Israel Trauma and Resiliency Center (MG and LLP), the Israel Science Foundation (TG and MG;1244/16), and the European Research Council Consolidator Grant (EF and DR;647209).…”
mentioning
confidence: 99%
“…The association between general negative affect and posttraumatic stress disorder (PTSD) has been well established (Brown et al., ; Marshall‐Berenz, Morrison, Schumacher, & Coffey, ; Souza et al., ). Moreover, although PTSD was originally conceptualized principally as a disorder of fear (American Psychiatric Association [APA], ; Foa & Kozak, ), there has been increasing recognition that negative emotions beyond fear are also strongly associated with PTSD (Dalgleish & Power, ; Hathaway, Boals, & Banks, ; Lancaster, Melka, & Rodriguez, ; Ozer, Best, Lipsey, & Weiss, ; Resick & Miller, ).…”
mentioning
confidence: 99%
“…For instance, Kashdan, Elhai, and Frueh (2006) found anhedonia to have a unique association with PTSD emotional numbing symptoms, and Brown et al. (2016) found that negative affect predicts reexperiencing and avoidance symptoms but not hyperarousal symptoms. It also appears there are distinct features of hyperarousal symptoms that negate the role of impulsivity in comparison to reexperiencing and avoidance/numbing symptoms.…”
Section: Discussionmentioning
confidence: 99%